Legal Protection of Women’s Rights in Afghanistan During the Taliban Regime of 2021-2022 and the State Responsibility - Alya Ananda Safitri; Sefriani Sefriani; Amalina Ghaisani (Lambung Mangkurat Law Journal, 2024)
This paper discusses women’s rights in Afghanistan during the Taliban regime from 2021 to 2022. Having seized power in Afghanistan by the Taliban in August 2021, a wide range of regulations seem to discriminate against women. The discriminatory restrictive regulations enforced by the Taliban have prevented women and girls in Afghanistan from receiving the same rights as men, such as access to education, employment, and access to public facilities. This is clearly inconsistent with The Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW). Given that Afghanistan ratified CEDAW in 2003, it guarantees the protection of women’s rights, it means that Afghanistan has become a state party, then Afghanistan has the responsibility to comply with this convention. This research uses the type of normative legal research - searching for material in the form of library materials or secondary data as sources in writing research. The purpose of this study is to find out how the legal protection of women’s rights during the Taliban regime considering that Afghanistan has ratified CEDAW. Furthermore, to find out whether Afghanistan can be held responsible for the restrictions on women’s rights imposed by the Taliban. The approach used in this study is the conceptual approach and the statute approach. This research also uses a historical approach and a case approach. This study finds the legal protection that Afghanistan has provided for women’s rights based on the ratification of CEDAW, namely the Law on Elimination of Violence against Women (EVAW). The Islamic Republic of Afghanistan’s Constitution also protects women’s rights. However, the EVAW law has not been enforced at all since the Taliban took over. It indicates that Afghanistan can be held responsible.